2011
DOI: 10.1021/nn203138t
|View full text |Cite
|
Sign up to set email alerts
|

125I-Labeled Gold Nanorods for Targeted Imaging of Inflammation

Abstract: For better examination of inflammation, we designed inflammation-targeted nuclear and optical dual-modality contrast agents prepared by I-125 radiolabeling of gold nanorods (GdNRs) conjugated with anti-intercellular adhesion molecule 1 (ICAM-1) antibody. The bioactivity and specific binding of the PEGylated 125I-ICAM-GdNRs conjugates to the ICAM-1 was validated through ELISA testing. Inflammation-targeted imaging was then conducted on an adjuvant-induced arthritic rat model which demonstrated an elevation of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 44 publications
1
47
1
Order By: Relevance
“…Numerous other reports have shown the labeling strategy of bonding radioiodine onto gold nanoparticles through direct incorporation 15-21. However, these methods allow only a small number of radioiodine labels to be incorporated on AuNPs; in addition, maintaining the stability of labeled radioiodine remains challenging within in vivo environments.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous other reports have shown the labeling strategy of bonding radioiodine onto gold nanoparticles through direct incorporation 15-21. However, these methods allow only a small number of radioiodine labels to be incorporated on AuNPs; in addition, maintaining the stability of labeled radioiodine remains challenging within in vivo environments.…”
Section: Resultsmentioning
confidence: 99%
“…This radiolabeling procedure has been proven to be efficient and stable as a result of the high affinity and strong binding of iodide ions with the surface of AuNPs 27. In the experiment, the 125 I‐labeled fAuNPs were delivered into human prostate cancer cells (DU145) for quantitative evaluation of cellular uptake efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…This, however, imposes demanding requirements on the resolution and sensitivity of PAI because most cancer cells are very small in size (≈10 μm) and exhibit little endogenous absorption contrast (except melanoma cells) 21, 22, 23, 24, 25, 26. To achieve high‐sensitivity PAI at the cellular level, exogenous contrast agent is preferably used to enhance optical absorption and amplify photoacoustic signal generation efficiency 27, 28, 29…”
Section: Introductionmentioning
confidence: 99%
“…Clearance studies showed fast renal elimination as confirmed by Tem of urine samples. Interestingly, the radiolabeling of 125 I was directly on the gold surface with good yield and stability [84][85][86]. There were about six 125 I isotopes per AuNp with serum stability tests showing more than 85% of 125 I remaining intact on AuNps after a 24 h incubation at 37°C, indicating the potential of this AuNp for tumor SpeCT imaging [87].…”
Section: Radiolabeled Gold Nanoparticles For Spect Imagingmentioning
confidence: 99%